PENGGUNAAN METODE LATIHAN UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA SISWA KELAS VI SD NEGERI 001 UKUI SATU KECAMATAN UKUI - Suyatin ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This background is the low class VI student learning outcomes SD Negeri 001 Ukui SatuKecamatan Ukui. This research is a class action, the study was conducted in two cycles. Thisstudy aims to improve science learning outcomes through the implementation of trainingmethods. The data used in this research is data teacher and student activities and studentlearning outcomes IPA. Based on the results of the study, data showed that the activities ofteachers and students and learning outcomes IPA increased in each cycle. This is evidencedby: (a) the activities of teachers in each cycle increases, in the first cycle obtained a score of19 (63%) with a category (simply perfect) and in cycle II increased with a score of 22 (73%)with katedori (perfect), Besides the student activity also increased, in the first cycle obtaineda score of 47 (60%) with a category (high) and the second cycle obtain a score of 52 (67%)with a category (high); and (b) Results to learn science is also increased, as evidenced by theincrease in the number of students learning completeness, in the first cycle the number ofstudents who reached the KKM is 10 students (77%) and the second cycle a total of 11students (85%).